A Practical Guide to SuFEx Chemistry: An Overview of S(VI)-SuFEx Linkers and Their Reactivity - Serbetci, Defne; Marraffa, Laura; Natho, Philipp; Andresini, Michael; Luisi, Renzo (Synthesis, 2024)
Sulfur(VI)–fluoride exchange (SuFEx) is a second generation, metal-free click chemistry concept introduced by Sharpless in 2014. Since the introduction of the concept, a large variety of synthetic methodologies to S(VI)-SuFEx hubs, and their derivatization with oxygen-, nitrogen-, and carbon-based nucleophiles have been developed. Herein, we provide a concise and practical overview for their preparation, SuFExability, inclusive of which substituents are tolerated. The stereoselective synthesis of aza-derivatives is also discussed.1 Introduction2 Synthesis of SuFEx Hubs2.1 Sulfonyl Fluorides2.2 Fluorosulfates2.3 Sulfamoyl Fluorides2.4 Sulfonimidoyl Fluorides2.5 Sulfuramidimidoyl Fluorides and Sulfurofluoridoimidates2.6 Sulfondiimidoyl Fluorides3 Reactivity of SuFEx Hubs3.1 Reactivity of Sulfonyl Fluorides3.2 Reactivity of Fluorosulfates3.3 Reactivity of Sulfamoyl Fluorides3.4 Reactivity of Sulfonimidoyl Fluorides3.5 Reactivity of Sulfurofluoridoimidates3.6 Reactivity of Sulfondiimidoyl Fluorides4 Stereochemical Considerations in SuFEx Chemistry5 Conclusion and Outlook
Keywords: click chemistry; SuFEx; sulfur; fluorine; S(VI)-hubs